Correlation Between Theoretical Classroom Instruction and Related Learning Experiences: Evidence From a Philippine Nursing University - Ryan Michael F. Oducado; Mary Kristine Q. Amboy; Ayesha C. Penuela; Rosana Grace Belo-Delariarte (International Journal of Scientific & Technology Research, 2019)
In nursing education, it is expected that theory underlies practice. However, studies have indicated nursing students still experience theory and practice gap. This study attempted to determine the relationship between theoretical classroom instruction and Related Learning Experiences (RLE) of nursing students. Using existing data set of nursing graduates in a Philippine Nursing University for a five year cohort (N=653) 653), this study employed a descriptive correlational research design. Pearson's correlation and simple linear regression were used to analyze the data . Results indicated that a significant relationship existed between theoretical classroom instruction and RLE performance of nursing students. Theoretical classroom instruction explained 64% of the variance in RLE. This study highlights the importance of good theoretical instruction in predicting the performance of nursing students in the practicum or RLE component of nursing education and training. Success in the didactic portion significantly contributes to the success of the practical part of the nursing curriculum. Nursing academic institutions must continually strive to promote the transfer of learning from classroom to actual care setting to help bridge the gap between theory and practice.
Keywords: 330; theory and practice gap; nursing; clinical performance; RLE performance; academic performance; nursing education